(untitled) - Mohamad Zaidi, Yahaya (2013)

(untitled)
In this research, carotene in the carrot (Daucus carota L.) was extracted by using Soxhlet extraction method. Carotene as a pigment that naturally contained in most vegetables is important source of nutrients. The main constituent of the carotenes which is beta-carotene was investigated. Two variables were varied in order to investigate the effect of drying time and solid-to-solvent ratio on the extraction and beta-carotene yield. Samples with different water content were prepared according to drying time of 3 h, 6 h, 9 h, 12 h, and 24 h at 60°C. The solvent used in the extraction process is 2-propanol with solid-to-solvent ratio of 1:4, 1:6, 1:8, and 1:10. After the extraction process, the mixture of carotene and solvent was separated using rotary evaporator in order to get extracted carotene. Then, the extracted carotene was analyzed using HPLC to determine the beta-carotene yield. From HPLC analysis, it shows the composition of beta-carotene in the extracted carotene increase as increasing drying time and solid-to-solvent ratio. This is due to less presence of water content in the sample and the excess of solvent used enhance the extraction process. The study found that optimal operating condition for this carotene extraction process was obtained at 12 h of drying time and 1:10 of solid-to-solvent ratio.